El barco de Camila : un cuento para dormir - Morgan, Allen, 1946-; Marton, Jirina; Rosa, Clara de la (Caracas : Ediciones Ekara, 2013)
Camila's father tells her a bedtime story in which Camila sails down the river to the sea with the animals she picks up along the way.
Translation of: Nicole's boat.
Keywords: Boats and boating -- Juvenile fiction; Bedtime -- Juvenile fiction; Children's stories, Spanish; Bedtime; Boats and boating; Children's stories, Spanish; Fiction; Juvenile works; Spanish language materials